Identifying Social Sustainability Considerations at the Design Stage of Public Procurement of Works in Ghana - Simon Kwabena Agyemang; Benjamin Baah (Cita Konsultindo Research Center, 2023)
Abstract Sustainability is a holistic modern construction that emphasizes environmental, social, and economical considerations. However, social sustainability has been at the tail end sustainability priorities. The study identifies social sustainability considerations at the design stage of public procurement of works in Ghana. In pursuant of this aim, the study employed a quantitative approach. Survey questionnaires were used obtain needed data from architects, project managers, engineers and quantity surveyors at D1K1 and D2K2 construction firms within Kumasi metropolis. Respondents were sampled using both convenience and snowball techniques. The use of descriptive analysis and the Mean Score Ranking enabled a thorough analysis of the data. The findings highlighted health and safety together with the satisfaction of stakeholders’ (end-users) expectations as important criteria in evaluating the social sustainability of publicly procured projects. These are also the often-incorporated social sustainability consideration in project design. As a consequence, health and safety must be given priority, incorporating redundancies in the health and safety precautions taken. Moreover, project stakeholders should be collaborated with at both the planning and design phases of construction, ensuring that the delivered project meets expectations.